A ANALISIS TINGKAT KEPUASAN PENGGUNA WEBSITE DINAS LINGKUNGAN HIDUP DAN KEHUTANAN PROVINSI RIAU MENGGUNAKAN EUCS - Muhammad Try Rizki (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
This study aims to identify the level of satisfaction of DISLHK users with the website of DISLHK using the EUCS method. EUCS is a means to distinguish between user expectations and the actuality of information systems to assess the level of user satisfaction with application systems. Based on interviews with website users at the Dislhk, several problems were found, such as errors occurring in some parts of the menu and difficulty understanding the appearance and features of the website. This research also provides recommendations for improvements to develop existing websites. In this study used 5 variables derived from end user computing satisfaction method. Questionnaires were distributed by giving respondents a google form in the form of questions related to research. Questionnaires were distributed to 108 respondents with 22 statements. The results show a total of 75.07%. It can be concluded that 5 variables from EUCS have provided satisfaction to users of the RIAU Province DISLHK website.